P.020 Long-term safety and tolerability of atogepant 60mg once daily for preventive treatment of migraine: a phase 3, 40-week, multicenter extension to the advance trial. (June 2022) - Klein, B; Miceli, R; Severt, L; McAllister, P; Mechtler, L; McVige, J; Diamond, M; Marmura, MJ; Leroux, E; Guo, H; Finnegan, M; Trugman, J
Abstract : Background: A phase 3 trial, ADVANCE (NCT03777059), demonstrated that atogepant, an oral, CGRP receptor antagonist dosed once daily, results in clinically meaningful reductions in mean monthly migraine days. This open-label extension for ADVANCE trial completers evaluated long-term safety and tolerability of atogepant over 40-weeks. Methods: Participants in this trial (NCT03939312), rolled over from the ADVANCE trial, were treated with atogepant 60mg once daily for 40-weeks, with a 4-week safety follow-up. Only safety data were collected. Results: 685 participants took at least one dose of study drug, 74.6% completed the 40-week treatment period; mean age of 41.8 years, 88.2% female, 84.4% white, and mean BMI of 30.58 kg/m2. Mean (SD) treatment duration was 233.6 (89.32) days. 62.5% of participants experienced a treatment-emergent adverse event (TEAE), with 8.8% considered treatment-related by the investigator; serious adverse events (SAEs) occurred in 3.4% of participants, none were treatment-related. The most frequent AEs leading to discontinuation was nausea (0.4%, n=3); the most frequent TEAEs observed included upper respiratory tract infection (5.5%, n=38) and urinary tract infection (5.3%, n=36). No deaths or hepatic safety issues were observed. Conclusions: Safety results are consistent with known safety profile of atogepant and support long-term safety and tolerability of once daily dosing of atogepant 60mg.